Cell-based Culture Informs Infectivity and Safe De-Isolation Assessments in Patients with Coronavirus Disease 2019. (24th October 2020) - Basile, Kerri; McPhie, Kenneth; Carter, Ian; Alderson, Susan; Rahman, Hossinur; Donovan, Linda; Kumar, Shanil; Tran, Tyna; Ko, Danny; Sivaruban, Tharshini; Ngo, Christine; Toi, Cheryl; et al.
Abstract: Background: The detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA by reverse-transcription polymerase chain reaction (PCR) does not necessarily indicate shedding of infective virions. There are limited data on the correlation between the isolation of SARS-CoV-2, which likely indicates infectivity, and PCR. Methods: A total of 195 patients with Coronavirus disease 2019 were tested (outpatients, n = 178; inpatients, n = 12; and critically unwell patients admitted to the intensive care unit [ICU] patients, n = 5). SARS-CoV-2 PCR-positive samples were cultured in Vero C1008 cells and inspected daily for cytopathic effect (CPE). SARS-CoV-2–induced CPE was confirmed by PCR of culture supernatant. Where no CPE was observed, PCR was performed on day 4 to confirm absence of virus replication. The cycle thresholds (Cts) of the day 4 PCR (Ctculture ) and the PCR of the original clinical sample (Ctsample ) were compared, and positive cultures were defined where Ctsample − Ctculture was ≥3. Results: Of 234 samples collected, 228 (97%) were from the upper respiratory tract. SARS-CoV-2 was isolated from 56 (24%), including in 28 of 181 (15%), 19 of 42 (45%), and 9 of 11 samples (82%) collected from outpatients, inpatients, and ICU patients, respectively. All 56 samples had Ctsample ≤32; CPE was observed in 46 (20%). The mean duration from symptom onset to culture positivity was 4.5 days (range, 0–18). SARS-CoV-2 was significantly more likely to be isolated from samples collected from inpatients ( P < .001) and ICU patients ( P < .0001) compared with outpatients, and in samples with lower Ctsample . Conclusions: SARS-CoV-2 culture may be used as a surrogate marker for infectivity and inform de-isolation protocols. Abstract : Isolation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in cell-based culture can inform infectivity and de-isolation protocols of coronavirus disease 2019, particularly for persons in whom SARS-CoV-2 RNA is persistently detected by nucleic acid testing despite clinical recovery.